KELAYAKAN LEMBAR KERJA PESERTA DIDIK DALAM SUBMATERI PENCEMARAN AIR KELAS X SMA - Pamela, Pamela; Hardigaluh, Basuki; Candramila, Wolly (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to determine the feasibility of Student Worksheet based on the analysis of the water quality of Ambawang River on the Sub Material of Water Pollution for first grade of high school. The study was conducted by descriptive method. The student worksheet consisted of learning goals, user instructions, research data, questions and conclusion of discussion material. This student worksheet was made through three stages, namely the preparation, revision and validation. The validation was carried out by 5 experts, consisting of 2 lecturers and 3 high school teachers. The validation data by five validators was calculated using the CVR and CVI formulas according to Lawshe (1975). The CVR and CVI value of the student worksheets was both 0,795 which mean that the student worksheets were not suitable for use and needed to be revised based on the recommedation from 5 validators.Â Keywords : Student Worksheet, Water Quality,Â  Submaterial of Water Pollution